2019
DOI: 10.1016/j.thromres.2019.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Rivaroxaban versus warfarin treatment among morbidly obese patients with venous thromboembolism: Comparative effectiveness, safety, and costs

Abstract: Introduction: Limited data exist on direct-acting oral anticoagulants in morbidly obese patients with venous thromboembolism (VTE). We compared clinical and health/economic outcomes with rivaroxaban versus warfarin for VTE treatment in morbidly obese patients. Materials and methods: This retrospective 1:1 propensity score matched cohort study analyzed data from 2 US claims databases. VTE patients initiating rivaroxaban or warfarin were identified who had diagnosis codes for morbid obesity (ICD-9:278.01,V85.4; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 57 publications
(76 citation statements)
references
References 32 publications
6
70
0
Order By: Relevance
“…Our use of codes for DVT and PE events is supported by a prior review that found high positive predictive values (65–95%) for identifying VTE events . Our VTE recurrence rates were higher (~6%) than those reported in one study (1–2%) but less than half the rates observed by another report (16–17%) . These differences may be attributed primarily due to the study designs and sources of data.…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…Our use of codes for DVT and PE events is supported by a prior review that found high positive predictive values (65–95%) for identifying VTE events . Our VTE recurrence rates were higher (~6%) than those reported in one study (1–2%) but less than half the rates observed by another report (16–17%) . These differences may be attributed primarily due to the study designs and sources of data.…”
Section: Discussionsupporting
confidence: 74%
“…With regard to safety, we found no significant difference in bleeding between treatment groups. Our major bleeding definition used a validated algorithm and was consistent with the approach used by others . Our bleeding event rates were similar to those reported by each of the prior studies (~1–2%) …”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations